Evaluation of the impact of various methods of analgesia onto duration of labor - Michał Michalczyk; Dorota Torbé; Andrzej Torbé (Kazimierz Wielki University, 2018)
Aim: The aim of the study was to compare the duration of particular stages of labor in cases of patient-controlled epidural anesthesia with parenteral use of opioid analgesics Material and methods: The study included 128 pregnant women ≥ 37 weeks, who were delivered vaginally in the Department of Obstetrics and Gynecology of the Pomeranian Medical University in Szczecin between 2013-2017. The women were divided into four groups: 1. PCEA (n = 33) women giving birth under PCEA in a horizontal position; 2. Pethidine (n = 24) women giving birth subjected to analgesia by parenteral supply of pethidine; 3. Fentanyl (n = 25) women giving birth subjected to analgesia by parenteral supply of fentanyl; 4. Control (n = 46) women giving birth without analgesia. In every group of patients the length of each stage of labor in minutes was assessed. Results: There were no significant differences in the length of the first and third stage of labor between the studied groups of patients. Similar results were obtained after the division of the patients in terms of parity. We found a statistically significant increase in the second stage of labor in patients undergoing epidural anesthesia controlled by the patient (p